The Influence of Destination Image, Novelty Seeking, and Information Quality in Social Media: The Case of Media News Company Indonesian Tourism on Instagram - Siti Zulzilah; Edy Prihantoro; Christiana Wulandari (Department of Communications, Universitas Islam Indonesia, 2019)
This study aims to determine how the influence of destination image, novelty seeking, and information quality in social media towards intention to visit a destination. Analysis was based on data collected from 400 respondents who followed Instagram account of @explorebandung, @explorejogja and @explorebali. Using the social information processing theory, we found that destination image, novelty seeking, and information quality on Instagram partially or simultaneously have a positive and significant effect on the visiting intention variable, with a fairly strong correlation value. Instagram, which is a new media, can be used as a trendy tool in digital tourism. The media news company on Instagram is considered effective if it's already known, interesting and has many followers. These findings are beneficial to both destination managers and the government in their efforts to improve and promote the Indonesian tourism as an attractive and unique destination to attract more tourists through social media..Keywords: Destination image; Novelty seeking; Information quality; Visiting intention; Social media network.